Association between RBC folate and lumbar bone mineral density in postmenopausal women, a cross-sectional study from NHANES 2009–2018 - Wei, Hua; Jin, Ziqi; Zhou, Liangji; Tang, Gangjian; Chai, Sheng; Che, Xiaoqiao; Tan, Yongxing; Zeng, Weiqing (Frontiers in Endocrinology, 2025)
BackgroundPostmenopausal women are at an increased risk of bone density reduction, with multiple factors implicated, including folate, a B vitamin whose impact on bone health is gaining attention. The purpose of this research was to examine the association between red blood cell (RBC) folate levels and lumbar bone mineral density (BMD) in postmenopausal women.MethodsWe performed a cross-sectional study to investigate the association between postmenopausal women’s lumbar BMD and RBC folate levels, using the data from the 2009–2018 National Health and Nutrition Examination Survey (NHANES). Participants were categorized into quartiles based on RBC folate levels (Q1-Q4). Univariate and multivariate regression models assessed the association between RBC folate levels and lumbar BMD, with threshold effect analysis performed.ResultsA total of 1315 postmenopausal women were included. RBC folate levels were positively associated with lumbar BMD. The trend analysis across the quartiles of RBC folate indicated a statistically significant trend in all models (P for trend: Model 1 = 0.020; Model 2 = 0.015; Model 3 = 0.037), suggesting that higher RBC folate levels are associated with increased lumbar BMD. In the unadjusted model 1, a 10 nmol/L increase in RBC folate was associated with a 0.0002 g/cm² increase in lumbar BMD (P=0.002509). The correlation was still significant (P=0.0006) even after age and race were taken into account (model 2). Further adjustment for multiple variables (model 3) showed a 0.0002 g/cm² increase in lumbar BMD per 10 nmol/L increase in RBC folate (P=0.0212). Threshold effect analysis revealed a breakpoint at 92.4 nmol/dL, suggesting a nonlinear relationship between RBC folate levels and lumbar BMD.ConclusionsPostmenopausal women’s RBC folate levels had a positive association with their lumbar BMD. Maintaining appropriate RBC folate levels may help preserve bone density and offer a fresh approach to avoiding osteoporosis in postmenopausal women.